WOOD AND PULPING PROPERTIES OF EUCALYPTUS UROPHYLLA AND ITS HYBRID GROWN BY SILVOPASTORAL AND CONVENTIONAL FOREST PRODUCTION MODELS - Souza, F. M. L. [UNESP]; Sansigolo, C. A. [UNESP]; Pupo, C. H. [UNESP]; Sereghetti, G. C. [UNESP] (Editura Acad Romane, 2017)
This study compares the wood and the pulping characteristics of Eucalyptus urophylla and the hybrid Eucalyptus urophylla x Eucalyptus grandis grown by two forest production models: the conventional system (3 x 3 m) and the silvopastoral one (9 x 2 m), in Ribas do Rio Pardo, MS, Brazil. The specific objectives were to compare the dendrometric parameters, the physical and chemical properties and the kraft pulping of the wood of the trees grown by both forest production models. 20 trees (2 species x 2 forest production models x 5 trees) from areas with similar soil characteristics (quartz sand soils), with an approximate age of 4.5 years, were collected. The production model had a greater influence on the wood's chemical composition, compared to the species. The silvopastoral system (9 x 2 m) significantly decreased the average basic density of the tree, increased the percentage of bark in the tree volume, increased the solubility of the wood in 1% NaOH, decreased the holocellulose content in the wood and increased the ash content. The chemical analyses showed better properties for kraft pulping of the E. urophylla wood from the conventional production system. Both the silvopastoral production (9 x 2 m) and the conventional (3 x 3 m) systems exhibited positive and expected outcomes in relation to basic density and chemical analysis conducted on the wood.
Keywords: spacing; silvopastoral system; dendrometric parameters; physical and chemical properties of wood; kraft pulping